A temperature gradient evaluation method for determining temperature dependent thermal conductivities. (22nd June 2021) - Wilhelmy, Sönke; Zimare, Anton; Lippmann, Stephanie; Rettenmayr, Markus
Abstract: Details of an experimental set-up and an evaluation method for determining temperature dependent thermal conductivities from one-dimensional steady-state temperature distributions are presented. The method is validated by obtaining continuous values for the thermal conductivities of pure Ni in the temperature range between 440 K and 740 K, brass (Cu-30Zn) in the temperature range between 350 K and 650 K and a titanium aluminide (TiAl-TNM) in the temperature range between 400 K and 700 K. The results are in agreement with available literature data. The reported scatter in the literature on conductivities is caused by microstructural or/and compositional differences, which highlights the necessity for swift and accurate experimental determination of thermal properties. For this, the proposed temperature gradient evaluation method is especially suited as it allows the direct determination of thermal properties within large temperature intervals using only a single experimental run. The experimental effort for a comprehensive study of a material is thus drastically reduced as compared to the conventional method of determining thermal conductivity from measured thermal diffusivities and heat capacities. The experimental set-up additionally allows the independent determination of thermal diffusivity as function of temperature. No prior knowledge of any material properties of a given sample is necessary.